Survey of Anxiety Level of Athletes of SMP 7 Karawang Barat In Futsal Sports - Latif Dwi Kurniawan; Maftuh Ahmad Laduni; Aldy Heri Wahyudi; Muhammad Arief Setiawan (UNIVERSITAS NEGERI MAKASSAR, 2024)
Anxiety is a situation where someone feels faced with a challenge. In sports, anxiety is very often experienced by athletes. Because during the match athletes often experience feelings of tension, worry, and uncertainty during the match. The lack of mental preparation of athletes greatly affects the athlete's performance. Likewise with futsal athletes. Futsal has the characteristics of a fast and dynamic game, Futsal is done on a small field, therefore it needs a strong mentality. As for athletes who are in junior high school who still have mental preparations that are not good enough. This study aims to determine the anxiety level of futsal athletes at SMPN 7 West Karawang. The results of the research that have been processed are 22.7% of female athletes who have high anxiety, and 9.1% of male athletes have high anxiety levels. The method used for this research uses a descriptive quantitative approach. With a sample size of 33 and a total of 10 questions. The results of the data show that the majority of SMP 7 West Karawang futsal athletes experience moderate anxiety. Women tend to feel anxious more often than men.